2020
DOI: 10.3390/en13215586
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Reverse Logistics of End-of-Life Vehicles: Bibliometric Analysis and Research Trend

Abstract: Under the background of the prompt development of the global economy and continuous improvement of environmental protection awareness, end-of-life vehicles (ELVs), as an essential part of “urban mineral”, have the substantial economic, resource, and environmental value. The research on reverse logistics of ELVs has developed rapidly, but the existing relevant reviews are based on unique research perspectives and do not fully understand the whole field. This work aims to help comprehend the research status of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…Bibliometric analysis of the literature review is the most famous and strong quantitative statistics technique used by different research teams who are dealing with high quantity of research publications and literature mapping in different field such as SSCM (Khan et al 2021a , 2021b ), waste management (Ranjbari et al 2021 ) and reverse logistics (He et al 2020 ), sustainable development (Du et al 2021 ), and technological innovations (Lee et al 2014 ). However, bibliometric analysis is very efficient in suggesting and guiding the future research direction of any field by providing a comprehensive evaluation of identified relationships among different factors of the area in publications, journals, citations, and co-citations (Ranjbari et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis of the literature review is the most famous and strong quantitative statistics technique used by different research teams who are dealing with high quantity of research publications and literature mapping in different field such as SSCM (Khan et al 2021a , 2021b ), waste management (Ranjbari et al 2021 ) and reverse logistics (He et al 2020 ), sustainable development (Du et al 2021 ), and technological innovations (Lee et al 2014 ). However, bibliometric analysis is very efficient in suggesting and guiding the future research direction of any field by providing a comprehensive evaluation of identified relationships among different factors of the area in publications, journals, citations, and co-citations (Ranjbari et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, Gao et al [50] recommended the WoS database for social sciences due to the high proportion of exclusive journals. Moreover, the database gained a high reputation and recognition in the scientific community, and thus, it became a primary source of citation data [51]. Therefore, WoS appears to be more suitable for searching and analyzing the scientific literature at the publication level [49].…”
Section: Records Identified Through Database Searchingmentioning
confidence: 99%
“…As noted in [20], future research should focus on building multipurpose and non-linear models, addressing carbon caps within a rigorous environmental policy, addressing additional uncertainties, and adopting better methods for solving.…”
Section: Territorial Location and Value Design Of The Reverse Logistics System's Nodesmentioning
confidence: 99%